2022
DOI: 10.1186/s12968-022-00885-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of left ventricular abnormalities with incident cerebrovascular events and sources of thromboembolism in patients with chronic Chagas cardiomyopathy

Abstract: Background Although Chagas cardiomyopathy is related to thromboembolic stroke, data on risk factors for cerebrovascular events in Chagas disease is limited. Thus, we assessed the relationship between left ventricular (LV) impairment and cerebrovascular events and sources of thromboembolism in patients with Chagas cardiomyopathy. Methods This retrospective cohort included patients with chronic Chagas cardiomyopathy who underwent cardiovascular magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…The main manifestations of chronic Chagas cardiomyopathy are heart failure, arrhythmia, and sudden cardiac death [42,45]. Chagas cardiomyopathy has also been independently associated with the risk of developing a stroke, with a significant cardioembolic risk secondary to the atrial fibrillation or LVT occurrence [42,45,46]. A recent study by Moreira HT et al, involving 330 patients with Chagas cardiomyopathy, found a prevalence of ischemic cerebrovascular events (ICE) of 20%, with 67 patients experiencing an ICE [46].…”
Section: Chagas Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The main manifestations of chronic Chagas cardiomyopathy are heart failure, arrhythmia, and sudden cardiac death [42,45]. Chagas cardiomyopathy has also been independently associated with the risk of developing a stroke, with a significant cardioembolic risk secondary to the atrial fibrillation or LVT occurrence [42,45,46]. A recent study by Moreira HT et al, involving 330 patients with Chagas cardiomyopathy, found a prevalence of ischemic cerebrovascular events (ICE) of 20%, with 67 patients experiencing an ICE [46].…”
Section: Chagas Cardiomyopathymentioning
confidence: 99%
“…Chagas cardiomyopathy has also been independently associated with the risk of developing a stroke, with a significant cardioembolic risk secondary to the atrial fibrillation or LVT occurrence [42,45,46]. A recent study by Moreira HT et al, involving 330 patients with Chagas cardiomyopathy, found a prevalence of ischemic cerebrovascular events (ICE) of 20%, with 67 patients experiencing an ICE [46]. Most patients were classified in New York Heart Association classes I or II (75%) with an average left ventricular ejection fraction of 39 ± 14% [46].…”
Section: Chagas Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The most characteristic segmental changes occur in the inferior, inferolateral, and apical segments of the left ventricle (LV). 4,6,[15][16][17] These segments are not always adequately assessed on two-dimensional (2D) studies, due to image shortening (which can exclude the apical segments from analysis) or to not including segments in the quantification of global function of Simpson's biplane method (which does not encompass the inferolateral segments). 6 Assessment of left ventricular ejection fraction (LVEF) is one of the main parameters for classification and staging of patients with Chagas disease; therefore, it is recommended to use methods that show high accuracy and reproducibility for estimating LVEF.…”
Section: Assessment Of Left Ventricular Function By 3d Echocardiographymentioning
confidence: 99%
“…Cardiac involvement represents the most feared manifestation, characterized by complications with high morbidity and mortality, such as heart failure, arrhythmias, and stroke. 1,2,4 In this scenario, echocardiography is the most commonly used complementary exam for assessment and follow-up of patients with Chagas disease, making it possible to analyze cardiac structure and function, detect intracavitary DOI: https://doi.org/10.36660/abcimg.20230093i thrombi, and assess secondary valve involvement. 1,5 In recent years, new techniques, such as three-dimensional (3D) echocardiography and the assessment of myocardial strain using the speckle-tracking method have shown to be promising in the assessment of cardiac mechanics in various clinical scenarios.…”
Section: Introductionmentioning
confidence: 99%